Time Synchronization - Busse, Marcel; Streichert, Thilo (Algorithms for Sensor and Ad Hoc Networks, 2007)
Time synchronization is an essential requirement in actually any distributed system such as sensor networks. Many applications require precise clocks, e.g., for the coordination of wake-up and sleeping times, TDMA schedules, ordering of sensed events, estimation of position information, and so on. The scope of time synchronization is to estimate (i) packet delay or latency, (ii) the offset between clocks, and (iii) the drift between clocks.